Novel Approaches in Synthesis of Heterocyclic Compounds: A Focus on 1,2,4-Triazoles and Their Pharmacological Potential - Jadhav R.S, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The synthesis of heterocyclic compounds, particularly 1,2,4-triazoles, has seen remarkable advancements owing to their significant pharmacological properties. This paper reviews novel approaches in the synthesis of 1,2,4-triazoles, including green chemistry methods, multicomponent reactions, metal-catalyzed reactions, and photocatalytic and electrochemical methods. Background: Heterocyclic compounds, particularly 1,2,4-triazoles, have gained significant attention due to their diverse pharmacological properties. The development of efficient synthetic methods for these compounds is crucial for advancing medicinal chemistry. Method: This paper reviews novel approaches in the synthesis of 1,2,4-triazoles, including green chemistry methods, multicomponent reactions (MCRs), metal-catalyzed reactions, and photocatalytic and electrochemical methods. The synthesis techniques are analyzed based on their efficiency, sustainability, and applicability. The pharmacological potential of 1,2,4-triazoles is discussed, focusing on their antimicrobial, anticancer, antiviral, anti-inflammatory, analgesic, anticonvulsant, and cardiovascular properties. Result: Novel synthetic approaches have significantly improved the efficiency, sustainability, and versatility of 1,2,4-triazole production. These methods provide higher yields, shorter reaction times, and environmentally friendly conditions. Pharmacological studies reveal that 1,2,4-triazoles exhibit a broad spectrum of biological activities, making them promising candidates for the development of new therapeutic agents. Conclusion: The synthesis of 1,2,4-triazoles through novel methods continues to advance, driven by the need for more efficient, sustainable, and versatile synthetic routes. These heterocyclic compounds hold great promise in various pharmacological applications, highlighting their importance in the development of new therapeutic agents. Ongoing research is likely to yield new derivatives with enhanced biological activities and improved therapeutic profiles.